Structural white matter changes in adults and children with posttraumatic stress disorder: a systematic review and meta-analysis - Siehl, Sebastian; King, John A.; Burgess, Neil; Flor, Herta; Nees, Frauke (NeuroImage: Clinical, 2018)
White matter plasticity occurs throughout life due to learning and can be a protective factor against as well as a vulnerability factor for the development of mental disorders. In this systematic review we summarize findings on structural white matter changes in children and adults with posttraumatic stress disorder (PTSD) and relate them to theoretical accounts of the pathophysiology of PTSD with a focus on the disturbed processing of contexts and associated problems in emotional and cognitive processing and PTSD symptomatology. We particularly examine studies reporting fractional anisotropy (FA) measured with diffusion tensor imaging (DTI). We further subdivided the studies in adult-onset PTSD with traumatic experience in adulthood, adult-onset PTSD with traumatic experience in childhood and children with PTSD. We included 30 studies comprising almost 1700 participants with 450 adults and 300 children suffering from PTSD. Our systematic review showed that for children with PTSD and adult-onset PTSD with childhood trauma, a decrease in FA in the corpus collosum, most prominently in the anterior and posterior midbody, the isthmus and splenium were reported. For adult-onset PTSD with traumatic experience in adulthood, changes in FA in the anterior and posterior part of the cingulum, the superior longitudinal fasciculus and frontal regions were found. Using GingerAle, we also performed a coordinate-based meta-analysis of 14 studies of adult-onset PTSD with traumatic experience in adulthood and did not find any significant clusters. Our results suggest that changes in white matter microstructure vary depending on traumatic experience and are associated with changes in brain circuits related to the processing of contexts. Finally, we present methodological considerations for future studies.